Middle Ear Recurrence in Nasopharyngeal Carcinoma: A Case Report - KORKUT, Arzu Yasemin; Teker, AYŞENUR; MERİÇ HAFIZ, AYŞENUR; KAHYA, Volkan; GEDIKLI, Orhan; SOMAY, Adnan (My University, 2011)
We report an extremely rare case of case of nasopharyngeal carcinoma (NPC) extending into the middle ear. A 38-year-old woman who presented with otorrhea, a polyp in the external auditory canal, and right facial palsy. The patient had undergone radio- and chemo-therapy for NPC 15 months previously. A computed tomography scan revealed the presence of a soft tissue density in the right mastoid air cells, middle ear, and external auditory canal, suggesting chronic otitis media with mastoiditis. The histopathologic examination of the mass demonstrated undifferentiated carcinoma that shared a similar histologic appearance with the original NPC. Otologic symptoms and signs may be the initial presentation of recurrent NPC. Therefore, physicians must be aware of the possibility of tumor recurrence in patients with a prior history of NPC who present with otorrhea and a polyp in the external auditory canal because awareness will allow early referral to an oncologist.
Keywords: Case Report